2013
DOI: 10.1111/mec.12472
|View full text |Cite
|
Sign up to set email alerts
|

Collembola, the biological species concept and the underestimation of global species richness

Abstract: Despite its ancient origin, global distribution and abundance in nearly all habitats, the class Collembola is comprised of only 8000 described species and is estimated to number no more than 50,000. Many morphologically defined species have broad geographical ranges that span continents, and recent molecular work has revealed high genetic diversity within species. However, the evolutionary significance of this genetic diversity is unknown. In this study, we sample five morphological species of the globally dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
87
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(98 citation statements)
references
References 54 publications
9
87
2
Order By: Relevance
“…Even for species that had been barcoded at other sites, their sequences were different from those collected from identical morphological species at the study site (i.e., <90% of sequence similarity). These results support the huge and hidden diversity in Collembola shown in previous studies (e.g., Porco et al 2012aPorco et al , 2012bCicconardi et al 2013) and suggest the need for generating more reference sequences of this group, more extensively at our study site as well as in various other geographic regions. At present, the construction of a locally collected database for mtCOI and mt16S genes will be needed to identify collembolan species from metabarcoding data.…”
Section: Selectivity and Sensitivity Assessed Using Natural Communitysupporting
confidence: 76%
“…Even for species that had been barcoded at other sites, their sequences were different from those collected from identical morphological species at the study site (i.e., <90% of sequence similarity). These results support the huge and hidden diversity in Collembola shown in previous studies (e.g., Porco et al 2012aPorco et al , 2012bCicconardi et al 2013) and suggest the need for generating more reference sequences of this group, more extensively at our study site as well as in various other geographic regions. At present, the construction of a locally collected database for mtCOI and mt16S genes will be needed to identify collembolan species from metabarcoding data.…”
Section: Selectivity and Sensitivity Assessed Using Natural Communitysupporting
confidence: 76%
“…This is in contrast to other studies on mites, insects, or other invertebrates, which have shown that presumed widespread taxa often represent complexes of cryptic species (Cicconardi, Fanciulli, & Emerson, 2013; Navia et al, 2013; Pérez-Portela, Arranz, Rius, & Turon, 2013; Schäffer et al, 2010). However, a clear geographic pattern can be seen in the haplotypes, which means that populations from different geographic locations do not show extensive gene flow between each other and dispersal may be limited.…”
Section: Discussioncontrasting
confidence: 94%
“…Such a general situation of poor knowledge is typical for the Collembola in many parts of the world (e.g. Cicconardi et al 2013), and will hamper efforts both to conserve this diversity (Cardoso et al 2011) and to understand which components of it are non-indigenous and may be having impacts on the indigenous fauna (see discussion in Roques et al 2009). …”
Section: Discussionmentioning
confidence: 99%